V. I. Starostenko: 90th anniversary and the 50th anniversary of the Specialized Scientific Council! - М.І. Орлюк (Геофизический журнал, 2025)
The article is dedicated to the contribution of Vitaliy Ivanovich Starostenko to the training of highly qualified personnel, namely, to his work in the Specialized Academic Council for the defense of dissertations for the degree of Doctor and Candidate of Sciences at the S.I. Subbotin Institute of Geophysics of the NAS of Ukraine.